Executive compensation, characteristics, and shareholder on tax avoidance - Mappadang, Agoestina; Mappadang, Jusuf Luther; Iskak, Jamaludin; Wijaya, Agustinus Miranda (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
This study aims to empirically prove the effect of executive compensation, executive characteristics, and executive share ownership on tax avoidance. Using a descriptive associative research method and secondary data, this study was shown in the consumer goods manufacturing corporation listed on the Indonesia Stock Exchange (IDX) from 2017–2021. The sampling method used purposive sampling. This research used 16 sample corporations, with a five-year research period of 5 years, so 80 objections were obtained for data processing. This study found that executive-compensation variables have no significant effect on tax avoidance, executive characteristics, and executive of the shareholder have a negative effect on tax avoidance.